ZINC OXIDE- PEROXIDASE BIOSENSOR: FABRICATION AND CHARACTERIZATION - H G. WANKHADE,; G.N.CHAUDHARI, (International Journal of Pharma and Bio Sciences, 2015)
Zinc oxide nanocomposite was prepared by sol gel method. Synthesized nanoparticle was characterized by X-ray diffraction and FT-IR spectroscopy. According to XRD analysis the crystallite size was found to be 30nm (approx) for ZnO. The formation of ZnO is confirmed by FT-IR. ZnO is used for the preparation of HRP/ ZnO/PVA/Au electrode. ZnO nanocomposite is mixed with PVA Solution and a thin layer is formed the gold surface, then HRP is immobilized on that by physisorption. ZnO/PVA/Au electrode is characterized by the SEM, Cyclic voltammetry and impedance analysis. All these techniques confirmed the formation of HRP/ ZnO/PVA/Au electrode. Cyclic voltammetry shows the defined redox peak.